I KNOW READ AND COUNT BUT I DON'T KNOW: A SPECIAL HISTORY AND SUI GÉNERIS - Rojas de la Puente, Edward Enrique; Arista, Guido Ayay (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
We describe the sui generis case of a couple of cohabitants and parents of 9 children that stands out in the light of the cognitive admiration and applause of many, because it shows how our characters considered illiterate in the eyes of the conventional educational world, arrived to be regular readers without having attended an educational center. The purpose of the study is to highlight the circumstances that forced the subjects of the sample to start alone in the field of reading. As a method, mayicatica was applied and the observation technique was used whose instruments were observation records and structured interviews. In conclusion, the collected experience shows that the learning of reading is not only conventional and its acquisition also responds to real communication needs.